Partnership Synergy for Improving Farmers' Economy in Sepakung Village, Semarang Regency - Widia, Syam; Witiastuti, Rini Setyo; Abiprayu, Kris Brantas; Wicaksari, Erisa Aprilia; Mudrikah, Saringatun (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: The main purpose of this service activity is to provide training on the development of business partnership networks that can open up more potential market opportunities, as well as have a positive impact on increasing the income of guava farmers in Sepakung Village. With the formation of a good partnership, it is hoped that a faster and more targeted business scheme can be built and be able to offer more competitive prices in the market. Method: The service methods carried out are: Needs Assessment, Development, Cooperation Exploration, Monitoring, and Evaluation. Practical Application: The results of the community service program show a positive impact on increasing the understanding of guava farmers regarding the development of partnership networks and marketing strategies. This increase in understanding can be seen from the results of the pre-test and post-test which showed a significant increase in various indicators. This shows that the training provided has successfully equipped farmers with practical skills that can be directly applied to expand market access, establish wider partnerships, and maximize profits from crops. Conclusion: Based on the results of community service activities in Sepakung Village, Semarang Regency, this program has succeeded in improving the understanding and skills of guava farmers in the development of partnership networks and marketing strategies. Pre-test and post-test data showed a significant increase, especially in the use of social media for promotion. The understanding of marketing strategies and market analysis has also improved.